Exploring knowledge management in civil society organisations: Sustaining commitment, advancing movement - Yanuar Nugroho; Mirta Amalia (The University of Manchester, Manchester Business School, 2008)
Civil society organisations (CSOs) have recently attracted much research attention, as they have become more central in social as well as economic and political dynamics, challenging and shaping the work of the state/public organisations and of the private institutions. Despite the fact that they are actually knowledge-intensive organisations, CSOs -like any other organisations- are faced with new challenges due to the advent of knowledge economy. Knowledge-capital in CSOs is highly diverse and this affects both the organisational performance and the civil society movement within which they are part of. Most of the knowledge in CSOs that has been driving and characterising civil society activities and realms is tacit in nature and is largely unmanaged. Consequently, in the long run, the organisations and their movement often become unstable despite efforts to manage their activities. We use the works of Polanyi and Nonaka to help address this problem and conceptualise the corpus of knowledge in CSOs. To anchor this conceptualisation, we feature the case of Indonesia where CSOs in a latecomer economy have been significantly influencing the work of public and private sectors. We find that managing tacit knowledge has been crucial to sustain the engagements with beneficiaries and networks. We propose taxonomy to understand different types of knowledge in CSOs and suggest a guiding principle to strategically manage it.
Keywords: 330; knowledge management; third sector; civil society; development; advocacy; commitment